DEVELOPING STUDENTS’ ABILITY IN SPEAKING BY USING DISCOVER LEARNING METHOD AT THE NINTH GRADE STUDENTS OF SMP NEGERI 1 LUAHAGUNDRE MANIAMOLO - Fau, Martina Meldawati; Impiani Zagoto (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
This research aimed to developing students’ ability in speaking by using discovery learning method. This research design by using classroom action research (CAR). This research was carried out in the ninth grade of SMP Negeri 1 Luahagundre Maniamolo which consisted of 22 students’ test. The data were analyzed by using qualitative and quantitative analysis to describe the students ability in speaking by using discovery learning method. . It showed that before conducting the research, the percentage of the students who can achieved the MCC was only 62% the students problem there are having the students have less motivation to have speaking ability because of their assumptions that English is a difficult in constructing sentences, the students have bad accent or pronounciation in speaking, the students have lack of vocabulary in constructing a sentences, the method in teaching speaking was less suitable to the students when having speaking topic, the researcher concludes that most of the students’ problem are in the technique of teaching. In collecting data the researcher using observation and test.Then after conducting the result, It can be seen from the students’ result in two cycles of research, where in the cycle I was 36%, passed or 64% were failed. while in the cycle II it was 84%, passed whereas 16% were failed. The total score gained in this cycle was 1.850 with the average score was 84. Thus, it can be stated that the students problem in speaking is solved by using discovery learning method. Discovery Learning Method is a way of achieving learning goals which emphasizes the students to learn by autodidact and to discovery the discussed material. For the Students, English teacher in general suggested should be highly motivated to know a lot of vocabulary and use them in practicing their speaking, and to use discovery learning method to develop the students ability in speaking